Influenza Vaccine Effectiveness for Prevention of Severe Influenza-Associated Illness Among Adults in the United States, 2019–2020: A Test-Negative Study. (20th May 2021) - Grijalva, Carlos G; Feldstein, Leora R; Talbot, H Keipp; Aboodi, Michael; Baughman, Adrienne H; Brown, Samuel M; Casey, Jonathan D; Erickson, Heidi L; Exline, Matthew C; Files, D Clark; Gibbs, Kevin W; Ginde, Adit A; et al.
Abstract: Background: Influenza vaccine effectiveness (VE) against a spectrum of severe disease, including critical illness and death, remains poorly characterized. Methods: We conducted a test-negative study in an intensive care unit (ICU) network at 10 US hospitals to evaluate VE for preventing influenza-associated severe acute respiratory infection (SARI) during the 2019–2020 season, which was characterized by circulation of drifted A/H1N1 and B-lineage viruses. Cases were adults hospitalized in the ICU and a targeted number outside the ICU (to capture a spectrum of severity) with laboratory-confirmed, influenza-associated SARI. Test-negative controls were frequency-matched based on hospital, timing of admission, and care location (ICU vs non-ICU). Estimates were adjusted for age, comorbidities, and other confounders. Results: Among 638 patients, the median (interquartile) age was 57 (44–68) years; 286 (44.8%) patients were treated in the ICU and 42 (6.6%) died during hospitalization. Forty-five percent of cases and 61% of controls were vaccinated, which resulted in an overall VE of 32% (95% CI: 2–53%), including 28% (−9% to 52%) against influenza A and 52% (13–74%) against influenza B. VE was higher in adults 18–49 years old (62%; 95% CI: 27–81%) than those aged 50–64 years (20%; −48% to 57%) and ≥65 years old (−3%; 95% CI: −97% to 46%) ( P = .0789 for interaction). VE was significantly higher against influenza-associated death (80%; 95% CI: 4–96%) than nonfatal influenza illness. Conclusions: During a season with drifted viruses, vaccination reduced severe influenza-associated illness among adults by 32%. VE was high among young adults. Abstract : During the 2019–2020 influenza season, characterized by circulation of drifted viruses with limited antigenic similarity to administered vaccines, influenza vaccination was moderately effective in preventing severe influenza disease, with 32% vaccine effectiveness in this multicenter study in the United States.